2014
DOI: 10.3390/nu6052077
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Mechanisms of the Food Contaminant Citrinin: Application of a Quantitative Yeast Model

Abstract: Mycotoxins are important food contaminants and a serious threat for human nutrition. However, in many cases the mechanisms of toxicity for this diverse group of metabolites are poorly understood. Here we apply live cell gene expression reporters in yeast as a quantitative model to unravel the cellular defense mechanisms in response to the mycotoxin citrinin. We find that citrinin triggers a fast and dose dependent activation of stress responsive promoters such as GRE2 or SOD2. More specifically, oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…We have previously shown that live cell reporter fusions in yeast are valuable and quantitative tools to characterize the acute transcriptional adaptation to CIT [28]. Here, we extend these studies to compare the impact of CIT and OTA on the induction of different stress-inducible genes.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…We have previously shown that live cell reporter fusions in yeast are valuable and quantitative tools to characterize the acute transcriptional adaptation to CIT [28]. Here, we extend these studies to compare the impact of CIT and OTA on the induction of different stress-inducible genes.…”
Section: Resultsmentioning
confidence: 76%
“…Moreover, OTA-induced transcription of GRE2 or SOD2 was already maximal at concentrations around 200 ppm (497 μM). We next tested the effect of the loss of Pdr5 function, which is a plasma membrane multidrug transporter critically involved in CIT extrusion [28]. As shown in Figure 1B, the deletion of Pdr5 provokes an enhanced transcriptional response to both CIT and OTA treatment at different doses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher concentration of citrinin in group C (CTN 250 µg*ml -1 ), in comparison to group B (CTN 100 µg*ml -1 ), caused significant (P < 0.05) reduction of Caco-2 cells, which means that anti-proliferative effects of CTN are dose-dependent. In the study of authors Pascual-Ahuir et al (2014) citrinin triggers a fast and dose dependent activation of stress responsive promoters. It has been reported that CTN stimulates ROS generation and c-Jun N-terminal kinase (JNK) activation for mitochondriadependent apoptotic signaling in human hepatoma G2 cells, and these apoptotic biochemical events are blocked by pretreatment with resveratrol, which exerts antioxidant effects (Chen and Chan, 2009).…”
Section: Discussionmentioning
confidence: 99%